A high-valence high-entropy iron defect type sodium ion battery positive electrode material, a preparation method and application thereof

CN122930907APending Publication Date: 2026-10-16SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611417119.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但现有高价高熵掺杂改性方案仍存在固有缺陷:高价掺杂阳离子与主体Fe2+之间存在较强静电斥力,容易驱动Fe2+迁移至Na+位点,产生Fe/Na原子混排现象

Benefits of technology

1、本发明设计了一种高价高熵元素掺杂与本征缺陷工程协同改性的Na4Fe3-x-y-zDxM1yM2z(PO4)2P2O7正极材料,其具备优异的宽温度适应性,在低温条件下能够缓解电化学极化,提升活性物质利用率,高温环境下也可维持晶体结构稳定,可在20 ℃~50 ℃宽温度区间内仍能表现出优异的电化学性能,并且正极材料在长循环过程中可以实现高度可逆的Fe2+/3+氧化还原和相变。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930907A_ABST
    Figure CN122930907A_ABST
Patent Text Reader

Abstract

The application discloses a high-valence high-entropy iron defect type sodium ion battery positive electrode material and a preparation method and application thereof, and has a chemical general formula of Na4Fe 3‑x‑y‑z D x M 1y M 2z (PO4)2P2O7; wherein, D represents iron site defects; M1 is selected from at least two kinds of rare earth elements; M2 is selected from at least two kinds of V, Ti, Sn, Hf, W, Nb and Mo; 0 2+ / 3+ The application adopts high-valence high-entropy element doping and intrinsic defect engineering modification, and the positive electrode material has excellent wide temperature adaptability, can relieve electrochemical polarization under low temperature conditions, improves active material utilization, can maintain crystal structure stability under high temperature environment, and exhibits excellent electrochemical performance in a wide temperature range, and the positive electrode material can realize highly reversible Fe 2+ / 3+ Oxidation-reduction and phase change in a long cycle process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery cathode material technology, specifically to a high-valence, high-entropy iron-defect sodium-ion battery cathode material, its preparation method, and its application. Background Technology

[0002] Sodium-ion batteries possess enormous application potential in large-scale energy storage systems and low-speed transportation due to the abundant reserves of sodium, low cost, and excellent safety performance. The cathode material is the core material that determines the electrochemical performance, cost, and operating temperature window of sodium-ion batteries. Currently, sodium-ion battery cathode materials mainly include three categories: polyanionic compounds, transition metal oxides, and Prussian blue compounds. Among polyanionic cathode materials, iron-based mixed phosphates (Na4Fe3(PO4)2P2O7, 1 C = 129 mAh·g) are particularly noteworthy. -1 Sodium-ion battery cathode material possesses significant advantages such as low raw material cost, environmental friendliness, and good crystal structure stability, making it a promising material for industrialization. However, several technical shortcomings remain to be addressed in practical applications: First, its discharge capacity and energy density are relatively low. The material synthesis process is prone to phase segregation, generating impurity phases (typically NaFePO4), leading to loss of active material and an actual output energy density of only about 290 Wh·kg⁻¹. -1 First, it is difficult to meet the ever-increasing energy demands of energy storage devices. Second, its rate performance is poor. The material has low intrinsic electronic conductivity and slow charge transfer kinetics. Under industrial thick-coated electrode conditions, it will produce severe polarization and stress accumulation. At high rates, the electrochemical performance will degrade significantly, and it will also cause problems such as electrode cracking and active material pulverization and shedding. Third, its low-temperature performance is poor. At low temperatures, the sodium ion diffusion kinetics deteriorate further. Coupled with the low intrinsic electronic conductivity, this will cause intensified electrochemical polarization and a significant decrease in the utilization rate of active materials, which limits the use of this material in a wide temperature range.

[0003] Currently, elemental doping is a common modification method to improve the intrinsic electronic conductivity and enhance the phase purity of polyanionic cathodes. This method is simple, requiring only adjustments to the raw material ratio, and even small amounts of doping can improve battery energy density and cycle performance, making it suitable for industrial production. Existing technologies typically introduce Cr at transition metal sites. 3+ Al 3+ Ti 4+ Sn 4+ Mo 6+Isovalent ions can improve phase purity and specific capacity by inducing sodium vacancies; simultaneously, doping elements can introduce impurity energy levels into the band structure, narrowing the band gap and improving electronic conductivity. However, the reversible capacity of most sodium-ion battery cathode materials is not ideal, and local phase transitions are prone to occur during deep charge-discharge processes, affecting the complete occurrence of redox reactions at the active center and structural stability during long-term cycling.

[0004] Existing research proposes using multi-element co-doping to construct high-entropy materials, leveraging the high-entropy "cocktail effect" to combine the advantages of multiple components and improve crystal structure stability. However, existing high-valence, high-entropy doping modification schemes still have inherent drawbacks: the high-valence doping cations and the host Fe... 2+ There is a strong electrostatic repulsion between them, which easily drives Fe 2+ Migration to Na + At sites, Fe / Na atom mixing occurs. Fe / Na mixing directly blocks sodium ion diffusion channels and reduces the redox efficiency of iron active sites. However, simply using high-valence, high-entropy doping cannot avoid this negative effect, making it difficult to simultaneously achieve high specific capacity, excellent rate performance, and long-cycle stability, nor can it effectively broaden the operating temperature range of the material. Therefore, there is an urgent need to develop a Na4Fe3(PO4)2P2O7-based cathode material that is easy to process, can simultaneously suppress impurity phase formation, overcome the Fe / Na mixing problem, improve electronic conductivity, and balance high capacity, high rate performance, long cycle life, and wide temperature adaptability. Summary of the Invention

[0005] The purpose of this invention is to solve the above-mentioned technical problems and provide a high-valence, high-entropy iron-defect-type sodium-ion battery cathode material, its preparation method, and its application. Through co-doping with high-valence, high-entropy elements and synergistic intrinsic defect engineering of iron sites, the material's phase purity and electronic conductivity are improved while Fe / Na mixing is suppressed, achieving a balance of high specific capacity, excellent rate performance, long-cycle stability, and wide operating temperature range.

[0006] The above-mentioned objective of this invention is achieved through the following technical solution: The first aspect of this invention provides a high-valence, high-entropy iron-defect sodium-ion battery cathode material, wherein the general chemical formula of the high-valence, high-entropy iron-defect sodium-ion battery cathode material is Na₄Fe. 3-x-y-z D x M 1y M 2z (PO4)2P2O7; Wherein, D represents an iron site defect; M1 is selected from at least two of rare earth elements, with a valence state of not less than +3; M2 is selected from at least two of V (vanadium), Ti (titanium), Sn (tin), Hf (hafnium), W (tungsten), Nb (niobium) and Mo (molybdenum), with a valence state of not less than +3; 0<x≤0.2, 0<y≤0.2, 0<z≤0.2, and 0<x+y+z≤0.6.

[0007] In the present invention, a series of high-valence elements are selected from transition metals and rare earth metals as dopants, and a Na4Fe co-modified by the synergy of high-valence high-entropy element doping and iron site intrinsic defect engineering is designed 3-x-y-z D x M 1y M 2z (PO4)2P2O7 material. The substitution of high-valence elements can not only effectively realize phase purification and improve the utilization rate of active substances, but also optimize the band structure and enhance the electronic conductivity. The actively introduced iron defects create a "repulsion buffer space" in the crystal lattice, effectively inhibiting the intrinsic Fe / Na anti-site phenomenon, and ensuring the accessibility of active iron sites and Na + the smoothness of diffusion channels. In addition, the high-valence elements have strong covalency with O, which can endow the adjacent Fe-O bonds with higher flexibility through polarization to buffer the lattice strain during charge and discharge; combined with the "cocktail" effect of high-entropy doping, the disordered distribution of multiple elements at the atomic scale provides structural support for the crystal lattice, which can greatly improve the structural stability of the material.

[0008] Further, the rare earth element M1 is selected from at least two of La (lanthanum), Y (yttrium), Nd (neodymium), Lu (lutetium), Sc (scandium) and Ce (cerium).

[0009] Further, La, Y, Nd, Lu, Sc and V are in the +3 valence state, Ti, Sn and Hf are in the +4 valence state, W and Nb are in the +5 valence state, and Mo is in the +6 valence state.

[0010] In a second aspect, the present invention provides a method for preparing the high-valence high-entropy iron-defect type cathode material for sodium-ion batteries according to the first aspect, comprising the following steps: S1. A sodium source, an iron source, a phosphorus source, a metal source corresponding to M1, and a metal source corresponding to M2 are taken according to a stoichiometric ratio, a reducing agent and water are added to prepare a mixed solution, and spray drying is performed to obtain a precursor powder; S2. The precursor powder is shaped, and pre-sintered at 300 ~350 °C in an inert atmosphere, then calcined at 500 ~600 °C, and cooled to obtain the high-valence high-entropy iron-defect type cathode material for sodium-ion batteries.

[0011] Further, in step S1, the sodium source is sodium acetate (CH3COONa); the iron source is ferric nitrate; the phosphorus source is ammonium dihydrogen phosphate (NH4H2PO4); the reducing agent is ascorbic acid (C6H8O6); and the metal sources corresponding to M1 and M2 are the corresponding nitrates, ammonium salts, chlorides, or organometallic salts.

[0012] Furthermore, the ferric nitrate is Fe(NO3)3·9H2O.

[0013] Further, in step S1, the inlet air temperature for the spray drying is 200°C. 240 ℃, outlet air temperature is 70 90℃.

[0014] Further, in step S2, the method for forming the precursor powder includes the following steps: compressing the precursor powder into tablets under a pressure of 8-12 MPa.

[0015] Further, in step S2, the pre-firing time is 2 seconds. 4 h.

[0016] Furthermore, in step S2, the calcination time is 8 hours. 12 h.

[0017] Furthermore, in step S2, the heating rate during the pre-calcination and calcination processes is 3-5 °C / min.

[0018] Furthermore, in step S2, the inert atmosphere is an argon atmosphere.

[0019] The third aspect of this invention provides an application of the high-valence, high-entropy iron-defect-type sodium-ion battery cathode material described in the first aspect in sodium-ion batteries.

[0020] The fourth aspect of the present invention provides a sodium-ion battery cathode sheet comprising the high-valence, high-entropy iron-defect sodium-ion battery cathode material described in the first aspect, a conductive agent, and a binder.

[0021] Furthermore, the conductive agent is a carbon material, which is selected from one or more of conductive carbon black, acetylene black, Ketjen black, activated carbon, carbon nanotubes, graphene, porous carbon, and carbon nanofibers.

[0022] Furthermore, the adhesive is polyvinylidene fluoride or polytetrafluoroethylene.

[0023] Furthermore, the mass ratio of the high-valence, high-entropy iron-defect sodium-ion battery cathode material, the conductive agent, and the binder is (7.5-9):(0.5-1.5):(0.5-1), preferably 8:1:1.

[0024] Furthermore, the method for preparing the sodium-ion battery positive electrode sheet includes the following steps: mixing a high-valence, high-entropy iron-defect sodium-ion battery positive electrode material, a conductive agent, and a binder to obtain a mixture; adding a solvent to the mixture and stirring to disperse it to obtain a slurry; coating the slurry onto a metal current collector and drying it to obtain the sodium-ion battery positive electrode sheet.

[0025] Furthermore, the solvent is selected from one or more of N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; the amount of solvent added is sufficient to completely dissolve the binder and uniformly disperse the carbon material to form a slurry.

[0026] Furthermore, the drying temperature is 110°C. 130 ℃, for 10 minutes 14 h.

[0027] The fifth aspect of the present invention provides a sodium-ion battery, comprising the sodium-ion battery positive electrode, negative electrode, separator, and electrolyte described in the fourth aspect.

[0028] Furthermore, the sodium-ion battery positive electrode, separator, and negative electrode are stacked sequentially and then encapsulated in the battery casing.

[0029] Specifically, the side of the sodium-ion battery positive electrode plate coated with high-valence, high-entropy iron defect type sodium-ion battery positive electrode material is in contact with the separator, and the other side of the separator is in contact with the negative electrode plate.

[0030] Furthermore, the diaphragm is a glass fiber diaphragm; the electrolyte is an ester electrolyte; the ester electrolyte contains sodium perchlorate (NaClO4) and a carbonate solvent.

[0031] Furthermore, the carbonate solvent is selected from one or more of dimethyl carbonate, ethylene carbonate, and ethyl methyl carbonate; the concentration of sodium perchlorate in the ester electrolyte is 1-5 mol·L⁻¹. -1 .

[0032] The above-described technical solution of the present invention has the following beneficial effects: 1. This invention designs a Na4Fe synergistic modification method involving high-valence, high-entropy element doping and intrinsic defect engineering. 3-x-y- z D x M 1y M 2z (PO4)2P2O7 cathode material exhibits excellent wide temperature adaptability. At low temperatures, it can alleviate electrochemical polarization and improve the utilization rate of active materials, while maintaining crystal structure stability at high temperatures. It exhibits excellent electrochemical performance over a wide temperature range of 20 ℃ to 50 ℃, and the cathode material can achieve highly reversible Fe during long-term cycling.2+ / 3+ Redox and phase transition.

[0033] 2. This invention adopts a preparation route combining spray drying and high-temperature sintering. By adjusting the raw material composition, the simultaneous construction of doping and iron defects can be achieved. The process parameters are controllable. The high-valence, high-entropy iron-defect sodium-ion battery cathode material obtained can achieve high specific capacity, excellent rate performance, and ultra-long cycle life. The entire preparation process is simple and controllable, and is compatible with existing production equipment, which is conducive to the industrial application of iron-based polyanion sodium-ion batteries. Attached Figure Description

[0034] Figure 1 Na4Fe prepared in Example 1 2.9 D 0.02 La 0.02 Ce 0.02 Mo 0.02 Sn 0.02 X-ray diffraction patterns of (PO4)2P2O7 and Na4Fe3(PO4)2P2O7 prepared in Comparative Example 1 are compared.

[0035] Figure 2 Na4Fe prepared in Example 1 2.9 D 0.02 La 0.02 Ce 0.02 Mo 0.02 Sn 0.02 Electrochemical performance curves of a sodium-ion battery assembled from (PO4)2P2O7 at 0.1 C rate for the first three cycles.

[0036] Figure 3 Na4Fe prepared in Example 1 2.9 D 0.02 La 0.02 Ce 0.02 Mo 0.02 Sn 0.02 Cycling performance of a sodium-ion battery assembled from (PO4)2P2O7 at 5 C rate.

[0037] Figure 4 Na4Fe prepared in Example 1 2.9 D 0.02 La 0.02 Ce 0.02 Mo 0.02 Sn 0.02 Sodium-ion batteries assembled with (PO4)2P2O7 were respectively... Charge-discharge curves at 0.1 C rate at 20 ℃ and 50 ℃. Detailed Implementation

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0039] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0040] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the materials and reagents used are commercially available.

[0041] Example 1 Na4Fe, a high-cost, high-entropy iron-defect-type cathode material for sodium-ion batteries 2.9 D 0.02 La 0.02 Ce 0.02 Mo 0.02 Sn 0.02 The preparation method of (PO4)2P2O7 includes the following steps: S1. Weigh 0.04 mol CH3COONa, 0.029 mol Fe(NO3)3·9H2O, 0.0002 mol La(NO3)3·6H2O, 0.0002 mol Ce(NO3)3·6H2O, 0.000029 mol (NH4)6Mo7O 24 ·4H2O, 0.0002 mol SnCl4·5H2O, 0.03 mol C6H8O6 and 0.04 mol NH4H2PO4 were placed in a beaker, and 80 mL of deionized water was added to prepare a clear mixed solution. The inlet and outlet air temperatures of the spray dryer were set to 220 ℃ and 80 ℃, respectively, and the precursor powder was prepared by spray drying.

[0042] S2. The precursor powder was pressed into discs with a diameter of 13 mm using a tablet press at 8 MPa. The discs were then transferred to a ceramic boat and pre-calcined in a tube furnace at 300 °C for 3 h under an argon atmosphere, followed by calcination at 510 °C for 10 h. After complete cooling, the mixture was ground to obtain a black powdery high-valence, high-entropy iron defect-type sodium-ion battery cathode material, Na4Fe. 2.9 D 0.02 La 0.02 Ce 0.02 Mo 0.02 Sn 0.02 (PO4)2P2O7.

[0043] Example 2 Na4Fe, a high-cost, high-entropy iron-defect-type cathode material for sodium-ion batteries 2.9 D 0.02 Y 0.02 Lu 0.02 Ti 0.02 Nb 0.02 The preparation method of (PO4)2P2O7 includes the following steps: S1. Weigh 0.04 mol CH3COONa, 0.029 mol Fe(NO3)3·9H2O, 0.0002 mol Y(NO3)3·6H2O, 0.0002 mol Lu(NO3)3·6H2O, 0.0002 mol C 16 H 36 O4Ti, 0.0002 mol C4H4NNbO9· x H2O, 0.03 mol C6H8O6 and 0.04 mol NH4H2PO4 were placed in a beaker, and 80 mL of deionized water was added to prepare a clear mixed solution. The inlet and outlet air temperatures of the spray dryer were set to 220 ℃ and 80 ℃, respectively, and the precursor powder was prepared by spray drying.

[0044] S2. The precursor powder was pressed into discs with a diameter of 13 mm using a tablet press at 8 MPa. The discs were then transferred to a ceramic boat and pre-calcined in a tube furnace at 300 °C for 3 h under an argon atmosphere, followed by calcination at 510 °C for 10 h. After complete cooling, the mixture was ground to obtain a black powdery high-valence, high-entropy iron defect-type sodium-ion battery cathode material, Na4Fe. 2.9 D 0.02 Y 0.02 Lu 0.02 Ti 0.02 Nb 0.02 (PO4)2P2O7.

[0045] Example 3 Na4Fe, a high-cost, high-entropy iron-defect-type cathode material for sodium-ion batteries 2.88 D 0.04 La 0.02 Ce 0.02 Mo 0.02 Sn 0.02 The preparation method of (PO4)2P2O7 includes the following steps: S1. Weigh 0.04 mol CH3COONa, 0.0288 mol Fe(NO3)3·9H2O, 0.0002 mol La(NO3)3·6H2O, 0.0002 mol Ce(NO3)3·6H2O, 0.000029 mol (NH4)6Mo7O 24 ·4H2O, 0.0002 mol SnCl4·5H2O, 0.03 mol C6H8O6 and 0.04 mol NH4H2PO4 were placed in a beaker, and 80 mL of deionized water was added to prepare a clear mixed solution. The inlet and outlet air temperatures of the spray dryer were set to 220 ℃ and 80 ℃, respectively, and the precursor powder was prepared by spray drying.

[0046] S2. The precursor powder was pressed into discs with a diameter of 13 mm using a tablet press at 8 MPa. The discs were then transferred to a ceramic boat and pre-calcined in a tube furnace at 300 °C for 3 h under an argon atmosphere, followed by calcination at 510 °C for 10 h. After complete cooling, the mixture was ground to obtain a black powdery high-valence, high-entropy iron defect-type sodium-ion battery cathode material, Na4Fe. 2.88 D 0.04 La 0.02 Ce 0.02 Mo 0.02 Sn 0.02 (PO4)2P2O7.

[0047] Example 4 Na4Fe, a high-cost, high-entropy iron-defect-type cathode material for sodium-ion batteries 2.82 D 0.02 La 0.04 Ce 0.04 Mo 0.04 Sn 0.04 The preparation method of (PO4)2P2O7 includes the following steps: S1. Weigh 0.04 mol CH3COONa, 0.0282 mol Fe(NO3)3·9H2O, 0.0004 mol La(NO3)3·6H2O, 0.0004 mol Ce(NO3)3·6H2O, 0.000057 mol (NH4)6Mo7O 24 ·4H2O, 0.0004 mol SnCl4·5H2O, 0.03 mol C6H8O6 and 0.04 mol NH4H2PO4 were placed in a beaker, and 80 mL of deionized water was added to prepare a clear mixed solution. The inlet and outlet air temperatures of the spray dryer were set to 220 ℃ and 80 ℃, respectively, and the precursor powder was prepared by spray drying.

[0048] S2. The precursor powder was pressed into discs with a diameter of 13 mm using a tablet press at 8 MPa. The discs were then transferred to a ceramic boat and pre-calcined in a tube furnace at 300 °C for 3 h under an argon atmosphere, followed by calcination at 510 °C for 10 h. After complete cooling, the mixture was ground to obtain a black powdery high-valence, high-entropy iron defect-type sodium-ion battery cathode material, Na4Fe. 2.82 D 0.02 La 0.04 Ce 0.04 Mo 0.04 Sn 0.04 (PO4)2P2O7.

[0049] Comparative Example 1 A method for preparing Na4Fe3(PO4)2P2O7, a cathode material for sodium-ion batteries, includes the following steps: S1. Weigh 0.04 mol CH3COONa, 0.03 mol Fe(NO3)3·9H2O, 0.03 mol C6H8O6 and 0.04 mol NH4H2PO4 into a beaker, add 80 mL of deionized water to prepare a clear mixed solution, set the inlet and outlet air temperatures of the spray dryer to 220 ℃ and 80 ℃ respectively, and prepare the precursor powder by spray drying.

[0050] S2. The precursor powder was pressed into discs with a diameter of 13 mm using a tablet press at 8 MPa. The discs were then transferred to a ceramic boat and pre-calcined in a tube furnace at 300 °C for 3 h under an argon atmosphere. After calcination at 510 °C for 10 h, the discs were completely cooled and then ground to obtain a black powdery unmodified sodium-ion battery cathode material Na4Fe3(PO4)2P2O7.

[0051] Powder X-ray diffraction tests were performed using Cu Kα radiation (λ=1.5406Å) on the Na₄Fe₄ prepared in Example 1. 2.9 D 0.0 2La 0.02 Ce 0.02 Mo 0.02 Sn 0.02 The X-ray diffraction patterns of (PO4)2P2O7 and Na4Fe3(PO4)2P2O7 prepared in Comparative Example 1 are compared as follows: Figure 1 As shown, the original Na4Fe3(PO4)2P2O7 contains the NaFePO4 impurity phase, and the introduction of high-valence, high-entropy elements can induce Na vacancies and effectively achieve phase purification.

[0052] Comparative Example 2 Na₄Fe, a high-cost, high-entropy sodium-ion battery cathode material 2.92 La 0.02 Ce 0.02 Mo0.02 Sn 0.02 The preparation method of (PO4)2P2O7 includes the following steps: S1. Weigh 0.04 mol CH3COONa, 0.0292 mol Fe(NO3)3·9H2O, 0.0002 mol La(NO3)3·6H2O, 0.0002 mol Ce(NO3)3·6H2O, 0.000029 mol (NH4)6Mo7O 24 ·4H2O, 0.0002 mol SnCl4·5H2O, 0.03 mol C6H8O6 and 0.04 mol NH4H2PO4 were placed in a beaker, and 80 mL of deionized water was added to prepare a clear solution. The inlet and outlet air temperatures of the spray dryer were set to 220 ℃ and 80 ℃, respectively, and the precursor powder was prepared by spray drying.

[0053] S2. The precursor powder was pressed into discs with a diameter of 13 mm using a tablet press at 8 MPa. The discs were then transferred to a ceramic boat and pre-calcined in a tube furnace at 300 °C for 3 h under an argon atmosphere, followed by calcination at 510 °C for 10 h. After complete cooling, the mixture was ground to obtain a black powdery high-valence, high-entropy sodium-ion battery cathode material, Na4Fe. 2.92 La 0.02 Ce 0.02 Mo 0.02 Sn 0.02 (PO4)2P2O7.

[0054] Comparative Example 3 Na4Fe, a cathode material for sodium-ion batteries 2.92 Mn 0.02 Mg 0.02 Ni 0.02 Cu 0.02 The preparation method of (PO4)2P2O7 includes the following steps: S1. Weigh 0.04 mol CH3COONa, 0.0292 mol Fe(NO3)3·9H2O, 0.0002 mol Mn(CH3COO)2·4H2O, 0.0002 mol Mg(CH3COO)2·4H2O, 0.0002 mol Ni(CH3COO)2·4H2O, 0.0002 mol Cu(CH3COO)2·H2O, 0.03 mol C6H8O6, and 0.04 mol NH4H2PO4 into a beaker, add 80 mL of deionized water to prepare a clear solution, set the inlet and outlet air temperatures of the spray dryer to 220 ℃ and 80 ℃ respectively, and prepare the precursor powder using the spray drying method.

[0055] S2. The precursor powder was pressed into discs with a diameter of 13 mm using a tablet press at 8 MPa. The discs were then transferred to a ceramic boat and pre-calcined in a tube furnace at 300 °C for 3 h under an argon atmosphere, followed by calcination at 510 °C for 10 h. After complete cooling, the mixture was ground to obtain a black powdered sodium-ion battery cathode material, Na4Fe. 2.92 Mn 0.02 Mg 0.02 Ni 0.02 Cu 0.02 (PO4)2P2O7.

[0056] Comparative Example 4 Na4Fe, a cathode material for sodium-ion batteries 2.9 D 0.02 V 0.02 W 0.02 Mo 0.02 Sn 0.02 The preparation method of (PO4)2P2O7 includes the following steps: S1, Weigh 0.04 mol CH3COONa, 0.029 mol Fe(NO3)3·9H2O, 0.0002 mol NH4VO3, and 0.000017 mol (NH4). 10 W 12 O 41 ·5H2O, 0.000029 mol (NH4)6Mo7O 24 ·4H2O, 0.0002 mol SnCl4·5H2O, 0.03 mol C6H8O6 and 0.04 mol NH4H2PO4 were placed in a beaker, and 80 mL of deionized water was added to prepare a clear solution. The inlet and outlet air temperatures of the spray dryer were set to 220 ℃ and 80 ℃, respectively, and the precursor powder was prepared by spray drying.

[0057] S2. The precursor powder was pressed into discs with a diameter of 13 mm using a tablet press at 8 MPa. The discs were then transferred to a ceramic boat and pre-calcined in a tube furnace at 300 °C for 3 h under an argon atmosphere, followed by calcination at 510 °C for 10 h. After complete cooling, the mixture was ground to obtain a black powdered sodium-ion battery cathode material, Na4Fe. 2.9 D 0.02 V 0.02 W 0.02 Mo 0.02 Sn 0.02 (PO4)2P2O7.

[0058] Comparative Example 5 Na4Fe, a cathode material for sodium-ion batteries 2.9 D 0.02 La 0.02 Ce0.02 Y 0.02 Sc 0.02 The preparation method of (PO4)2P2O7 includes the following steps: S1. Weigh 0.04 mol CH3COONa, 0.029 mol Fe(NO3)3·9H2O, 0.0002 mol La(NO3)3·6H2O, 0.0002 mol Ce(NO3)3·6H2O, 0.0002 mol Y(NO3)3·6H2O, 0.0002 mol Sc(NO3)3·6H2O, 0.03 mol C6H8O6, and 0.04 mol NH4H2PO4 into a beaker, add 80 mL of deionized water to prepare a clear solution, set the inlet and outlet air temperatures of the spray dryer to 220 ℃ and 80 ℃ respectively, and prepare the precursor powder using the spray drying method.

[0059] S2. The precursor powder was pressed into discs with a diameter of 13 mm using a tablet press at 8 MPa. The discs were then transferred to a ceramic boat and pre-calcined in a tube furnace at 300 °C for 3 h under an argon atmosphere, followed by calcination at 510 °C for 10 h. After complete cooling, the mixture was ground to obtain a black powdered sodium-ion battery cathode material, Na4Fe. 2.9 D 0.02 La 0.02 Ce 0.02 Y 0.02 Sc 0.02 (PO4)2P2O7.

[0060] Comparative Example 6 Na4Fe, a cathode material for sodium-ion batteries 2.94 D 0.02 La 0.02 Sn 0.02 The preparation method of (PO4)2P2O7 includes the following steps: S1. Weigh 0.04 mol CH3COONa, 0.0294 mol Fe(NO3)3·9H2O, 0.0002 mol La(NO3)3·6H2O, 0.0002 mol SnCl4·5H2O, 0.03 mol C6H8O6 and 0.04 mol NH4H2PO4 into a beaker, add 80 mL of deionized water to prepare a clear solution, set the inlet and outlet air temperatures of the spray dryer to 220 ℃ and 80 ℃ respectively, and prepare the precursor powder by spray drying.

[0061] S2. The precursor powder was pressed into discs with a diameter of 13 mm using a tablet press at 8 MPa. The discs were then transferred to a ceramic boat and pre-calcined in a tube furnace at 300 °C for 3 h under an argon atmosphere, followed by calcination at 510 °C for 10 h. After complete cooling, the mixture was ground to obtain a black powdered sodium-ion battery cathode material, Na4Fe. 2.94 D 0.02 La 0.02 Sn 0.02 (PO4)2P2O7.

[0062] Test Example 1 80 mg of sodium-ion battery cathode materials prepared in Examples 1-4 and Comparative Examples 1-6 were mixed and ground evenly with 10 mg of conductive carbon black and 10 mg of polyvinylidene fluoride to obtain a mixture. The mixture was then mixed and stirred evenly with 0.7 mL of N-methylpyrrolidone to obtain a slurry. The slurry was evenly coated on one side of a carbon-coated aluminum foil and vacuum-insulated in a vacuum oven at 120 °C for 12 h. The foil was then cut into sodium-ion battery cathode sheets with a diameter of 12 mm.

[0063] A sodium-ion battery is assembled using the aforementioned sodium-ion battery positive electrode, glass fiber separator, negative electrode, and ester electrolyte. The side of the sodium-ion battery positive electrode coated with slurry is in contact with the glass fiber separator, and the other side of the glass fiber separator is in contact with the negative electrode. The positive electrode, glass fiber separator, and negative electrode are then sealed together in a battery casing. The ester electrolyte is formed by dissolving NaClO4 in dimethyl carbonate, ethylene carbonate, and ethyl methyl carbonate (volume ratio 1:1:1), with a NaClO4 concentration of 1 mol·L⁻¹. -1 .

[0064] The iron defect amount (Fe / P ratio) in the cathode material was characterized using inductively coupled plasma mass spectrometry (Inductively Coupled Plasma Mass Spectrometry, M90, Jena, Germany). XRD results were refined using GSAS software, and the Fe / Na mixing concentration was calculated based on the occupancy information of Fe and Na sites. The electrochemical performance of the sodium-ion battery (1 C = 129 mAh·g⁻¹) was tested using a NEWARE multichannel battery testing system at room temperature, -20 °C, and 50 °C within a voltage range of 1.8–4.3 V. -1 The test results are as follows: Figure 2-4 As shown in Table 1: Table 1

[0065] As can be seen from Table 1, the high-valence, high-entropy iron defect-type cathode material Na4Fe prepared in Example 1... 2.9 D 0.02 La 0.02 Ce 0.02 Mo0.02 Sn 0.02 (PO4)2P2O7 exhibits the best electrochemical performance and excellent high and low temperature performance. The electrochemical performance curves of the sodium-ion battery assembled with it at 0.1 C rate for the first three cycles are shown below. Figure 2 As shown, it exhibits high reversible capacity and excellent charge-discharge reversibility; the cycle performance at 5 C rate is shown in the figure below. Figure 3 As shown, the capacity retention rate was 96.3% after 500 laps; respectively The charge-discharge curves at 20 ℃ and 50 ℃ at a 0.1 C rate are as follows: Figure 4 As shown, sodium-ion batteries still exhibit good electrochemical performance over a wide temperature range.

[0066] A comparison of Example 1 and Comparative Example 1 shows that the unmodified Na4Fe3(PO4)2P2O7 material has a larger Fe / Na mixing concentration, Fe 2+ / 3+ The redox reaction activity and utilization rate are low, resulting in poor battery capacity and cycle stability. A comparison between Example 1 and Comparative Example 2 shows that the introduction of high-valence, high-entropy elements can improve Fe to some extent. 2+ / 3+ Redox activity is improved, enhancing the rate performance of the battery. However, since Comparative Example 2 did not introduce iron defects, the high-valence doped cations and the host Fe... 2+ The electrostatic repulsion between Fe and Na intensifies Fe / Na mixing, affecting the material's capacity. A comparison between Example 1 and Comparative Example 3 shows that high-entropy doping of low-valence elements does not exacerbate mixing, but low-valence cations cannot maximize the activation of Fe. 2+ / 3+ Redox activity was observed, and the discharge specific capacity and rate performance of the battery in Comparative Example 3 were poor. A comparison of Examples 1 and 2 with Comparative Examples 4 and 5 shows that while high-entropy doping of elements in M1 or M2 alone can alleviate Fe / Na mixing and improve initial discharge capacity to some extent, the lack of synergistic effects between elements results in poor cycle stability and low-temperature performance. A comparison of Example 1 and Comparative Example 6 shows that low-entropy doping of high-valence elements (two or fewer doping elements) can effectively suppress Fe / Na mixing, but it cannot achieve effective Fe... 2+ / 3+ The redox reaction is activated, and due to the absence of a high-entropy stabilizing effect, the sodium-ion battery assembled in Comparative Example 6 has poor cycle stability.

[0067] In summary, this invention achieves a dual improvement in both energy density and crystal structure stability of sodium-ion batteries. The battery not only exhibits ultra-high cycle stability but also operates stably within a wide temperature range of -20 ℃ to 50 ℃, which helps to promote the practical application and development of high-performance sodium-ion batteries.

[0068] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art should understand that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A high-valence, high-entropy iron-defect-type sodium-ion battery cathode material, characterized in that, The chemical formula of the high-valence, high-entropy iron-defective sodium-ion battery cathode material is Na₄Fe₂. 3-x-y-z D x M 1y M 2z (PO4)2P2O7; wherein, D represents an iron site defect; M1 is selected from at least two of the rare earth elements, with a valence state of no less than +3; M2 is selected from at least two of V, Ti, Sn, Hf, W, Nb and Mo, with a valence state of no less than +3; 0<x≤0.2, 0<y≤0.2, 0<z≤0.2, and 0<x+y+z≤0.

6.

2. The high-valence, high-entropy iron-defect-type sodium-ion battery cathode material according to claim 1, characterized in that, Said rare earth element M1 is selected from at least two of La, Y, Nd, Lu, Sc and Ce.

3. A method for preparing the high-valence, high-entropy iron-defect-type sodium-ion battery cathode material according to claim 1 or 2, characterized in that, comprising the following steps: S1. A sodium source, an iron source, a phosphorus source, a metal source corresponding to M1, and a metal source corresponding to M2 are taken according to the stoichiometric ratio, a reducing agent and water are added to prepare a mixed solution, and spray drying is performed to obtain a precursor powder; S2. The precursor powder is shaped and subjected to an inert atmosphere at 300 °C. Pre-fired at 350 ℃, then at 500 ℃ The high-valence, high-entropy iron-defect sodium-ion battery cathode material was obtained by calcination at 600 °C and cooling.

4. The preparation method according to claim 3, characterized in that, In step S1, the sodium source is sodium acetate; the iron source is ferric nitrate; the phosphorus source is ammonium dihydrogen phosphate; the reducing agent is ascorbic acid; the metal sources corresponding to M1 and M2 are the corresponding nitrates, ammonium salts, chlorides, or organometallic salts; and the inlet air temperature for spray drying is 200°C. 240 ℃, outlet air temperature is 70 90 ℃.

5. The preparation method according to claim 3, characterized in that, In step S2, the method for forming the precursor powder includes the following steps: compressing the precursor powder into tablets under a pressure of 8-12 MPa; the pre-calcination time is 2... 4 h; the calcination time is 8 h. 12 h.

6. An application of the high-valence high-entropy iron-defect sodium-ion battery positive electrode material as defined in claim 1 or 2 in a sodium-ion battery.

7. A sodium-ion battery positive electrode, characterized in that, comprising the high-valence high-entropy iron-defect sodium-ion battery positive electrode material as defined in claim 1 or 2, a conductive agent and a binder.

8. The sodium-ion battery positive electrode sheet according to claim 7, characterized in that, Said conductive agent is a carbon material, and said carbon material is selected from one or more of conductive carbon black, acetylene black, Ketjen black, activated carbon, carbon nanotubes, graphene, porous carbon and carbon nanofibers; said binder is polyvinylidene fluoride or polytetrafluoroethylene; the mass ratio of said high-valence high-entropy iron-defect sodium-ion battery positive electrode material, conductive agent and binder is (7.5-9):(0.5-1.5):(0.5-1).

9. A sodium-ion battery, characterized in that, comprising the sodium-ion battery positive electrode sheet as defined in claim 7 or 8, a negative electrode, a separator and an electrolyte.

10. The sodium-ion battery according to claim 9, characterized in that, The diaphragm is a glass fiber diaphragm; the electrolyte is an ester-based electrolyte; the ester-based electrolyte contains sodium perchlorate and a carbonate solvent; the carbonate solvent is selected from one or more of dimethyl carbonate, ethylene carbonate, and ethyl methyl carbonate; the concentration of sodium perchlorate in the ester-based electrolyte is 1-5 mol·L⁻¹. -1 .